CULTURAL VALUES MATTER: A SHIFTING INSTITUTIONALISATION IN THE PRIVILEGE OF YOGYAKARTA SPECIAL REGION - Harsono, Dwi; Suranto (Universitas Negeri Yogyakarta, 2024)
This article evaluates the policy of Special Autonomy (Privileges) in the Special Region of Yogyakarta (DIY), which has been in place since 2012 and focuses on institutional strengthening based on local cultural values. Although designed to strengthen local governance and cultural institutions, the impact of such policies on poverty alleviation remains limited. Using a qualitative descriptive approach, this study explores the perceptions of stakeholders and the public, as well as examines policy documents and budget allocation reports. The findings reveal that the implementation of the five privileged affairs has gradually shifted from land and space affairs to institutional and cultural development. The changing nomenclature of the government’s organisation has been allowing the further distribution of special funds to the kalurahan office, as it is part of the institutional development of the government. This program will hopefully have a leverage effect the the surrounding society to participate in the application of cultural values in the region. However, most programs remain bureaucratic and top-down, limiting their potential to improve social welfare. The study concludes that a reorientation towards community-based programs rooted in cultural empowerment is necessary to realise the constitutional mandate of prosperity and tranquillity. This article contributes to the discourse on asymmetric decentralisation and its alignment with the effectiveness of public policy in culturally distinct regions.